Notational analysis of serve and return location and rally length and their effects on point winning in world-class table tennis players - Ng, Yang Theng (2017)
The study aimed to analyse the characteristics of serve location, return location and rally length among male world-class players and whether these significantly affect rally characteristics such as final shot outcome and point outcome. 20 International Table Tennis Federation (ITTF) sanctioned men table tennis matches were randomly selected among matches played from 2015-2016 between the top 10 ranked male table tennis players in the world based on the January 2017 ITTF world rankings. The performance indicators examined were serve location (n = 1913), return location (n = 1722), rally length (n = 1913), point outcome (n = 1913) and final shot outcome (n = 1913). Chi-squared test for independence was used to test for association between the following pair of variables: Serve location and point outcome, return location and point outcome, rally length and point outcome, serve location and final shot outcome, return location and final shot outcome, rally length and final shot outcome. There was a significant relationship between rally length and point outcome and there were some observable serve and return strategies. In conclusion, this study serves as a reference for coaches and players to analyse and compare their performance with that of world class players, identify strengths and weaknesses and devise new strategies to improve their performance in competition. Keywords: Notational Analysis, Performance Indicators, Serve Location, Return Location